Policies for agricultural productivity growth and poverty reduction in rural Ethiopia - Abro, Z.A.; Alemu, B.A.; Hanjra, Munir A. (Elsevier, 2014)
Increasing the productivity of smallholder agriculture holds the key to poverty reduction. The empirical literature is limited to ascertain the linkages and the implications for policy uptake in Ethiopia. We examine the impact of growth in agricultural productivity on household poverty dynamics in rural Ethiopia using a panel data set (1994–2009). Findings suggest that government policies aimed at reducing poverty should adopt a growth plus approach—designing policy interventions to support agricultural productivity growth, plus to protect assets and enhance market access for rural households in the country.